Clinical outcomes of total laryngectomy for laryngeal carcinoma - Bajaj, Y; Shayah, A; Sethi, N; Harris, AT; Bhatti, I; Awobem, A; Loke, D; Woodhead, CJ (Kathmandu University Medical Journal, 2010)
Background: Controversy exists as to the management of advanced laryngeal carcinoma. In general primary radical surgery is favoured. Objective: The aim of this study was to analyse the clinical outcome of patients having total laryngectomy for cancer of larynx. Materials and methods: This study was a retrospective case note review and questionnaires were used for evaluating voice handicap. These laryngectomies included in this study were performed by the senior author (CJW) from January 2001 till June 2007 at Leeds General Infirmary, Leeds. Some of the patients had partial or total pharyngectomy in addition to total laryngectomy. Results: In this study a total of 59 patients were included. Seventeen (28.8%) of these patients had preoperative radiotherapy and laryngectomy was performed for residual or recurrent disease. The initial TNM staging of the tumour ranged from T1N0 to T4N2C. Tracheoesophageal puncture for speech prosthesis was done in 48/59 (81.4%) patients. Post-operative complications were seen in 30.5% (18/59) patients. In this study group 9 patients (15.2%) developed pharyngocutaneous fistulas. For communication 31/51 (60.8%) patients were using speech valves. In this study 30.4% had minimal, 26.1% moderate and the rest 43.4% feeling severely handicapped with regards to voice use after total laryngectomy. Five year survival after laryngectomy in this study was 65.2%. Conclusion: Long term disease control and survival is achievable with total laryngectomy with or without postoperative radiotherapy with minimal risks in patients with advanced carcinoma of larynx. Key words: Laryngectomy; Larynx; Carcinoma DOI: 10.3126/kumj.v7i3.2734 Kathmandu University Medical Journal (2009) Vol.7, No.3 Issue 27, 258-262